RESEARCH TRENDS OF SELF ESTEEM AND RELATE FACTORS IN PEDIATRIC BURN SURVIVOR: FROM STUDY DESIGN TO DATA ANALYSIS - Saputro, Teguh Dwi; Dewi, Yulis Setiya; Wahyudi, Andri Setiya (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction: Burns is a form of trauma that often causes severe organ and tissue damage. Sleep disorders in children after burns are less studied so that they also affect wound healing, social development, behavior, and growth. The purpose of this research to explore research trends in sleep disorders in children with burns, from study design to data analysis.Method: This study used content analysis of a number of articles that have been published  in PubMed, EMBASE, CINAHL, Cochrane, Web of Science, Scopus, APAPsychInfo, and Clinicaltrials.gov from 2011 to 2022 with the main focus of sleep disorders research in burn patients.Results: Of the 1888 articles that have been found, 22 research articles have been selected. There were fluctuations in the number of publications on sleep disorders in burn patients from 2011 to 2022. The current study reveals that  in the past ten years, the number of publications focusing on sleep disorders in burn patients has increased.  The most research subjects were children who experienced sleep disorders due to burns. T-test is an analysis method that is often used.Conclusions: In light of the findings of this study, several recommendations have been put forward for future research that underlie research to reduce sleep disturbances in burn patients as a primary focus. Some of these recommendations include increasing the diversity of types of research that have not been done much and choosing more appropriate data analysis techniques.